The impact of death-related media information on consumer value orientation and scope sensitivity - Jiang, Yuwei (2019)
This research examines how incidental exposure to death-related information in the media affects consumers’ value orientation and scope sensitivity to marketing stimuli. Five studies demonstrate that, in contrast to thoughts about one's own mortality, exposure to death-related information in the media can shift consumers’ focus from extrinsic to intrinsic values. This leads them to pay less attention to the marketing stimuli, which are generally associated with extrinsic values, and consequently results in lower sensitivity to the magnitude of products and services. These effects are reversed when the marketing stimuli are associated with intrinsic values. Moreover, we found that exposure to death-related media information will generate effects similar to those of mortality salience when the information is perceived to be self-relevant and thus could induce death anxiety. The authors discuss implications and possible extensions.